2005
DOI: 10.1021/ja054500+
|View full text |Cite
|
Sign up to set email alerts
|

The α-Helix Folds More Rapidly at the C-Terminus Than at the N-Terminus

Abstract: The helix-coil dynamics of different sections of an alpha-helical model peptide were observed separately by nanosecond temperature jump experiments with IR detection on a series of isotopically labeled peptides. The results show that the helix-coil dynamics of the alpha-helical C-terminus are faster than those of the N-terminus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 17 publications
7
83
2
Order By: Relevance
“…Indeed, the precise position of the Amide I’ bands is slightly dependent on the secondary structure. This technique has already brought many impressive results [8,9]. However, it suffers from a lack of quantitative estimation of the helix content.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the precise position of the Amide I’ bands is slightly dependent on the secondary structure. This technique has already brought many impressive results [8,9]. However, it suffers from a lack of quantitative estimation of the helix content.…”
Section: Introductionmentioning
confidence: 99%
“…Protein fragments or designed peptides with welldefined secondary structures have been used in a variety of studies to probe the initial steps of protein folding. a-Helical peptides of various sizes and sequences were found to fold in the submicrosecond time range [8][9][10][11][12][13][14]. Also several studies on b-hairpins have been performed [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…T-jump relaxation dynamics using an N-terminal fluorescence probe revealed faster helix unfolding in the N-terminal region compared with the decrease in average helix content (8). Site-specific IR studies on 13 C-labeled peptides, in contrast, suggested only little position dependence of the relaxation times after a T-jump (22,(25)(26)(27). These studies gave insight into the kinetics of perturbationinduced helix unfolding, but they did not yield information on the dynamic properties of ␣-helices under equilibrium conditions.…”
mentioning
confidence: 97%